A thinking reed Pascal's voice, yesterday and today - Williams, Stephen N. 1952- (Cascade Books, 2023)
"Blaise Pascal (1623-62) was a provocative and important thinker. Both the range and the influence of his work is immense. His Pensees ("Thoughts"), unfinished and composed of fragments, is widely regarded as a classic of Christian apologetics. In this volume, the reader is introduced to this work, with a view to both describing what Pascal says and assessing its present value. After introducing the man and his life, Pascal's views on reason and the heart, and on human wretchedness and greatness, are discussed before asking in a final chapter, "Would you bet on God?" An appendix treats Pascal and modernity. Four hundred years on, Pascal's voice can still be heard. Four hundred years on, we still need to heed it. Pascal does not simply speak from the mind to the mind. He speaks as a person to persons"--
Keywords: Pascal, Blaise -- 1623-1662; Pascal, Blaise / 1623-1662; Pascal, Blaise / 1623-1662 / Influence; Apologetics; Philosophers / France / 17th century / Biography